Strategi Pemasaran Kayu Olahan Indonesia di Pasar Internasional - Atmosasmito, Suratmadi (STIE Kesatuan, 2000)
This research is intended to conceive a framework for increasing sawntimber export by analyzing the ways of transaction that were implemented by exporter. The data was obtained from the related institutions and publications. The result of this study can be summarized in ten important points that are significantly determine the strategy of Indonesiaâs sawntimber marketing in international market. The ten points were: (1) Utilization of tehnology improvement and experience, (2) Recognition of the importer cultures, (3) Extention of the importer, (4) Understanding the producers, (5) The variety of FOB, (6) Ecolabelling issue, (7) Sustainable Forest Management, (8) The degradation of forests, (9) The environmental issue as a barrier to entry, (10) The domination of plywood in the wood product market. Keywords: Strategi pemasaran; Kayu olahan; Pasar International